2015
DOI: 10.3892/ijmm.2015.2365
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin accelerates reendothelialization and ameliorates intimal hyperplasia in balloon-injured rat carotid artery via the upregulation of endothelial cell autophagy

Abstract: Delayed reendothelialization and intimal hyperplasia (IH) contribute to the failure of vascular interventions. Curcumin (Cur) has been used for various types of diseases with antioxidant, antiproliferative and anti-inflammatory effects. However, investigations involving the application of Cur in inhibiting IH are limited. The aim of the present study was to evaluate the potential therapeutic effects of Cur and its underlying mechanisms on a rat model of carotid artery (CA) intimal injury. In vitro, an endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The UPS impairment or inhibition will result in accumulation of misfolded and aggregated protein leading to compensative activation of autophagy ( Korolchuk et al, 2009 ; Jänen et al, 2010 ; Wang and Wang, 2015 ), aimed to clear up the aggregated or misfolded proteins that were previously thought to be targeted exclusively by the UPS ( Ding et al, 2007 ; Graziotto et al, 2012 ). Curcumin possesses the properties of proteasome inhibitor and autophagy inducer ( Milacic et al, 2008 ; Han et al, 2012 ; Chen et al, 2015 ). In the present study, we found that curcumin administration significantly suppressed peptidase activities of 20S proteasome, and compensatively activated autophagy under palmitate treatment ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UPS impairment or inhibition will result in accumulation of misfolded and aggregated protein leading to compensative activation of autophagy ( Korolchuk et al, 2009 ; Jänen et al, 2010 ; Wang and Wang, 2015 ), aimed to clear up the aggregated or misfolded proteins that were previously thought to be targeted exclusively by the UPS ( Ding et al, 2007 ; Graziotto et al, 2012 ). Curcumin possesses the properties of proteasome inhibitor and autophagy inducer ( Milacic et al, 2008 ; Han et al, 2012 ; Chen et al, 2015 ). In the present study, we found that curcumin administration significantly suppressed peptidase activities of 20S proteasome, and compensatively activated autophagy under palmitate treatment ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a significant association between ER stress and insulin resistance in endothelial cells ( Lenna et al, 2014 ; Gustavo Vazquez-Jimenez et al, 2016 ).When this ER stress is blocked pharmacologically, a complete recovery of insulin sensitivity is achieved ( Ozcan et al, 2004 ). Interestingly, curcumin acts as an inhibitor of both proteasome and ER stress ( Milacic et al, 2008 ; Han et al, 2012 ; Afrin et al, 2015 ; Chen et al, 2015 ; Rashid and Sil, 2015 ; Wang et al, 2016 ). Given that the proteasome pathway and autophagy has been demonstrated to interact each other ( Korolchuk et al, 2009 ; Jänen et al, 2010 ; Wang and Wang, 2015 ), we rationally and logically speculated that curcumin might maintain ER proteostasis through activating autophagy, leading to suppression of ER stress with subsequent improvement of insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…23 Chen et al demonstrated that Cur could accelerate reendothelialization and ameliorate intimal hyperplasia of rat carotid artery tissues by promoting endothelial cell autophagy. 24 In addition, a previous study has shown that inflammatory cells can participate in intimal restenosis by secreting inflammatory factors to stimulate the increase of VSMCs and their migration to the subintima. 25 The proliferation of VSMCs and the carotid artery restenosis following vascular injury are associated with the increase in the levels of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…Disappointingly, several lines of evidence suggest that approximately 40–50% of these vein grafts ultimately result in stenosis and even occlusion . The primary cause of stenosis of vein grafts is oxidative stress caused by injury of the endothelium .…”
Section: Introductionmentioning
confidence: 99%
“…Injection of MSCs has been utilized to alleviate atherosclerosis, myocardial ischaemia and vascular balloon injury . Experiments have shown that oxidative stress exists in vascular intima and the blood circulation following both vein grafting and vascular injury, after a short period of time and lasting for several weeks . Furthermore, recent studies have demonstrated that excessive and/or persistent stimulation of oxidative stress can reduce the functions of MSCs and increase apoptosis .…”
Section: Introductionmentioning
confidence: 99%